The π Complex of the Hydronium Ion Frozen on the Pathway of Electrophilic Aromatic Substitution. Issue 26 (30th August 2016) - Růžičková, Zdeňka; Holub, Josef; Melichar, Petr; Moncol, Jan; Wann, Derek A.; Fanfrlík, Jindřich; Růžička, Aleš; Hnyk, Drahomír
Abstract : A very rare crystal was prepared consisting of a 2D aromatic (toluene) together with a weakly coordinating 3D aromatic ( closo ‐1‐CB11 H12 – ) and a hydronium ion, and this crystal was analyzed by using X‐ray diffraction and high‐level quantum‐mechanical calculations. The nature of the crystal arrangement made it possible to detect the frozen π complex that would originate during protonation of toluene by the acidic hydronium ion. Abstract : A ternary crystal that consists of a weakly coordinating and 3D aromatic anion (1‐CB11 H12 – ), hydronium (H3 O + ), and toluene is obtained, and its crystal‐packing forces are computationally analyzed. The presence of this anion enables the other two components of the crystal to be viewed as a frozen π complex that originates during proton exchange occurring at the 2D aromatic toluene.